Reciprocity and critical reflection as the key to social justice in service learning: A case study. Issue 2 (4th March 2017) - Asghar, Mandy; Rowe, Nick
Abstract: Service learning is experiential education that encourages students as socially responsible and active citizens working in and with members of the community. We consider how these ideas illuminate the ambitions of a unique service-learning opportunity known as 'Converge', a university partnership with a health care provider that brings together students and users of mental health services in a variety of educational activities. We are particularly concerned in this article to address the criticism that service learning can exploit marginalised groups for the benefit of student education. We propose that reciprocal relationships which challenge established ideas and practices, together with engaging students in critical and informed analysis are key components in ensuring that service learning is socially just.